Analyzing the divergence and development of business models for urban farming - Annelise de Jong; Rebecka Milestad; Maria J. Bustamante; Michael Martin (Urban Agriculture & Regional Food Systems)
Abstract Urban farming initiatives are increasingly considered to contribute to the development of sustainable cities—not only regarding increased circularity and resource efficiency but also to address and improve the social and economic dimensions of city regions’ sustainability. However, there is a lack of knowledge regarding upscaling and how urban farms can become more viable. The aim of this study was to explore the current business development of urban farming as well as the drivers and barriers for their upscaling. The study employs a qualitative case study on 10 commercial urban farms in the Stockholm region, where data were collected through semi‐structured interviews. The analysis showed that the market consists of a large variety of urban farm types, with business models adapted to their situation. The competition for gaining a larger market share in terms of yield is challenging, so some farms have instead aimed to offer their technological knowledge or diverse packages of other societal and professional services. This shift toward technology and services is apparent for several of the urban farms in the study and requires a completely new set of skills for employees. By expanding through decentralized food production, on‐farm gastronomy, technical product‐service systems, or by providing societal services, there are ample opportunities for increasing the market share of the farms.